of Multiple Recessions with Minimally Invasive Technique: A Case Report - Pradhan, Ameena (Journal of Nepalese Society of Periodontology and Oral Implantology, 2017)
Recession of the gingival margin remains a highly prevalent problem for its impact on both aesthetics and periodontal health. The search for a perfect root coverage technique has led to the development of a number of innovative surgical procedures to achieve consistently better and more predictable results. This case report introduces a simple minimal invasive surgical method “Modified Semilunar Coronally Advanced Flap Technique” to treat gingival recession in multiple teeth. This technique has shown additional advantage of minimal surgical site with no shortening of vestibule, better coronal mobility and stability of repositioned flap.